Evaluation of by-products from the biodiesel industry as fermentation feedstocks for the production of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) by Cupriavidus necator - García, I. L. (2013)
Utilization of by-products from oilseed-based biodiesel production (crude glycerol, rapeseed meal hydrolysates) for microbial polyhydroxyalkanoate (PHA) production could lead to the replacement of expensive carbon sources, nutrient supplements and precursors for co-polymer production. Batch fermentations in shake flasks with varying amounts of free amino nitrogen led to the production of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (P(3HB-co-3HV)) with a 2.8–8% 3HV content. Fed-batch fermentations in shake flasks led to the production of 10.9 g/L P(3HB-co-3HV) and a 55.6% P(3HB-co-3HV) content. NaCl concentrations between 2 and 6 g/L gradually became inhibitory to bacterial growth and PHA formation, whereas in the case of K2SO4, the inhibitory effect was observed only at concentrations higher than 20 g/L. Differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) and nuclear magnetic resonance (13C NMR) demonstrated that the incorporation of 3HV into the obtained P(3HB-co-3HV) lowered glass transition temperature, crystallinity and melting point as compared to polyhydroxybutyrate. Integrating PHA production in existing oilseed-based biodiesel plants could enhance the viability and sustainability of this first generation biorefinery.